2017
DOI: 10.1242/jeb.161562
|View full text |Cite
|
Sign up to set email alerts
|

A role for tight junction-associated MARVEL proteins in larval sea lamprey (Petromyzon marinus) osmoregulation

Abstract: This study reports on tight junction-associated MARVEL proteins of larval sea lamprey () and their potential role in ammocoete osmoregulation. Two occludin isoforms (designated Ocln and Ocln-a) and a tricellulin (Tric) were identified. Transcripts encoding , and were broadly expressed in larval lamprey, with the greatest abundance of in the gut, liver and kidney, in the gill and skin, and in the kidney. Ocln and Ocln-a resolved as ∼63 kDa and ∼35 kDa MW proteins, respectively, while Tric resolved as a ∼50 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Previous reports have shown that IPW acclimation of ammocoetes leads to a reduction in circulating Na + and Cl − levels and causes general body hydration (Kolosov et al ., ), whereas SW acclimation of transformed juveniles increases blood Na + and Cl − levels (Beamish, ; Ferreira‐Martins et al ., ; Reis‐Santos et al ., ). In teleosts, previous studies have indicated that paracellular permeability and mRNA abundance of TJ proteins are altered in gill and skin epithelia on exposure or acclimation to IPW ( e.g ., Chasiotis, Kolosov, Bui, & Kelly, ; Gauberg et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous reports have shown that IPW acclimation of ammocoetes leads to a reduction in circulating Na + and Cl − levels and causes general body hydration (Kolosov et al ., ), whereas SW acclimation of transformed juveniles increases blood Na + and Cl − levels (Beamish, ; Ferreira‐Martins et al ., ; Reis‐Santos et al ., ). In teleosts, previous studies have indicated that paracellular permeability and mRNA abundance of TJ proteins are altered in gill and skin epithelia on exposure or acclimation to IPW ( e.g ., Chasiotis, Kolosov, Bui, & Kelly, ; Gauberg et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The identity of annotated genes was confirmed using sequence identity comparison and NCBI BLAST. RNA extraction from lamprey tissues and cDNA synthesis (mentioned earlier) were conducted according to previously published protocols (Kolosov et al ., ). PCR products employing gene‐specific primers were sequenced, and their identity was confirmed by comparing with vertebrate homologues available in the NCBI database as well as by comparing with original genomic data in Ensembl Genome Browser.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations